Commodities in asset management - Nadeshda Demidova-Menzel; Thomas Heidorn (Frankfurt School of Finance & Management, 2007)
The investment in commodities is starting to be more important during the last years. The paper describes the characteristics of financially important commodities. In many cases a passive investment in an index is most suitable. As the GSCI is found to be the most important, its underlying futures are analyzed. The change of risk-return relationships in equity and bond portfolios including commodities is discussed. The paper shows that the effects differ substantially during different holding periods. Especially during times of high inflation and strong equity markets, commodities were a sensible addition. Still, the total performance from 1976 to 2006 was not convincing. This paper reveals that the performance does not mainly depend on the spot return but more on roll and collateral return.
urn:nbn:de:101:1-20080827282
Keywords: G11; G15; G24; 330; Commodities; investable commodities; commodity future; commodity index; GSCI; portfolio optimization with commodities; spot return; roll return; collateral return